3D printing composite material and preparation method thereof
Patent Information
- Application Number
- CN202611113992.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-27
AI Technical Summary
[0004]但是,矿物类固体废弃物粉体直接用于热塑性3D打印复合材料时,仍难以适配熔融挤出类增材制造对材料连续稳定成型的要求,容易出现粉体分散不均、界面结合不足以及熔融挤出稳定性不足等问题,进而影响打印过程的连续性和打印制品的层间结合性能
[0005]本发明旨在一定程度上解决相关技术中的技术问题之一。为此,本发明提供了一种3D打印复合材料及其制备方法,能够提高固废矿物粉体在热塑性树脂基体中的分散稳定性和界面结合性能,并改善3D打印复合材料在熔融挤出成型时的稳定性。
Smart Images

Figure CN122628516B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials, and more specifically to a 3D printed composite material and its preparation method. Background Technology
[0002] 3D printing is a molding technology that uses digital models to deposit materials layer by layer to form three-dimensional products. Fused deposition modeling, particle extrusion molding, and screw extrusion additive manufacturing are all additive manufacturing methods that involve extruding thermoplastic materials after melting. Thermoplastic materials used in these molding methods typically need to have suitable melt flowability, continuous extrusion stability, interlayer bonding performance, and dimensional stability.
[0003] Current thermoplastic materials used in 3D printing typically use thermoplastic resins such as polylactic acid, polyethylene terephthalate, polybutylene adipate / terephthalate, and polybutylene succinate as matrix materials. To reduce material costs or improve product rigidity, existing technologies also include adding inorganic or mineral fillers to the thermoplastic resins. Mineral solid wastes such as coal gangue, fly ash, steel slag, furnace slag, red mud, silica-alumina construction waste, ceramic waste, and glass powder contain a significant amount of inorganic mineral components, possessing potential value as filler components in thermoplastic 3D printing composite materials.
[0004] However, when mineral solid waste powders are directly used in thermoplastic 3D printing composites, they still struggle to meet the continuous and stable forming requirements of melt extrusion additive manufacturing. Problems such as uneven powder dispersion, insufficient interfacial bonding, and inadequate melt extrusion stability easily arise, affecting the continuity of the printing process and the interlayer bonding performance of the printed product. Therefore, there is an urgent need to provide a 3D printing composite material suitable for thermoplastic melt extrusion additive manufacturing to improve the compatibility of solid waste mineral powders in this type of material system. Summary of the Invention
[0005] This invention aims to address one of the technical problems in related technologies to a certain extent. To this end, this invention provides a 3D printing composite material and its preparation method, which can improve the dispersion stability and interfacial bonding performance of solid waste mineral powder in a thermoplastic resin matrix, and improve the stability of the 3D printing composite material during melt extrusion molding.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A 3D printing composite material includes a thermoplastic resin matrix and modified solid waste mineral powder dispersed in the thermoplastic resin matrix. The modified solid waste mineral powder includes a powder body and an organic modification layer formed on the surface of the powder body; The powder body is obtained by pre-treatment of solid waste mineral powder. The pre-treatment includes impurity removal treatment, desalination treatment, thermal activation treatment and particle size control treatment. The solid waste mineral powder is derived from mineral solid waste. The organic modified layer is formed by the surface interaction between the surface modifier and the surface of the powder body; The thermoplastic resin matrix and the modified solid waste mineral powder are melt-blended to form the 3D printing composite material.
[0007] Optionally, by weight, the 3D printing composite material comprises 45-85 parts of the thermoplastic resin matrix, 10-45 parts of the modified solid waste mineral powder, 3-15 parts of toughening agent, 2-8 parts of compatibilizer, 0.2-2 parts of lubricant, 0.1-1 parts of antioxidant, and 0-5 parts of functional additives; wherein the organic modified layer of the modified solid waste mineral powder is formed by 0.5-3 parts of surface modifier.
[0008] Optionally, the thermoplastic resin matrix includes one or more of polylactic acid, recycled polyethylene terephthalate, polyethylene terephthalate, polybutylene adipate / terephthalate, polybutylene succinate, polyhydroxyalkanoates, and polypropylene carbonate.
[0009] Optionally, the mineral solid waste includes one or more of the following: coal gangue, fly ash, steel slag, furnace slag, red mud, siliceous aluminum building solid waste, ceramic waste, and glass powder, and the total content of SiO2, Al2O3, CaO, Fe2O3 and MgO in the solid waste mineral powder is not less than 60wt%.
[0010] Optionally, the modified solid waste mineral powder has a D50 particle size of 1-15 μm, a D90 particle size of less than 35 μm, a moisture content of less than 1.0 wt%, and a chloride content of less than 1.0 wt%.
[0011] Optionally, the surface modifier includes one or more of silane coupling agents, titanate coupling agents, aluminate coupling agents, stearic acid, and dopamine; the compatibilizer includes one or more of maleic anhydride-grafted polylactic acid, maleic anhydride-grafted polyethylene, maleic anhydride-grafted polypropylene, epoxy chain extender, and acrylate copolymers; the toughening agent includes one or more of poly(butylene adipate / terephthalate), poly(butylene succinate), thermoplastic polyurethane, ethylene-vinyl acetate copolymer, and acrylate elastomers; the functional additives include one or more of biochar, bamboo charcoal powder, lignin, nano-silica, nano-calcium carbonate, flame retardants, antibacterial agents, UV stabilizers, or deodorizers; the lubricant includes one or more of polyethylene wax, zinc stearate, calcium stearate, ethylene bis-stearamide, and silicone powder; and the antioxidant includes one or more of hindered phenolic antioxidants or phosphite antioxidants.
[0012] Optionally, the 3D printed composite material is used for fused deposition modeling, particle extrusion molding, or screw extrusion additive manufacturing; wherein, when used for fused deposition modeling, the printing temperature is 180–260°C, the heated bed temperature is 40–90°C, and the printing speed is 20–120 mm / s.
[0013] Furthermore, the present invention also provides a method for preparing the aforementioned 3D printing composite material, comprising the following steps: S1, mineral solid waste is subjected to crushing, screening, magnetic separation and desalination in sequence to obtain desalinated solid waste mineral raw materials; S2, the desalinated solid waste mineral raw material is dried and calcined to activate it, and calcined product is obtained; S3, the calcined product is subjected to mechanical ball milling to obtain a powder body; S4, the powder body is surface modified by using a surface modifier to form an organic modified layer on the surface of the powder body, thereby obtaining modified solid waste mineral powder. S5, mix the thermoplastic resin matrix, the modified solid waste mineral powder, toughening agent, compatibilizer, lubricant, and antioxidant to obtain a mixture; S6, the mixture is melt-blended, extruded, cooled, pelletized and dried to obtain the granular 3D printing composite material.
[0014] Optionally, after step S6, step S7 is further included, in which the granular 3D printing composite material is subjected to filament extrusion treatment by a single screw extruder to prepare 3D printing filament, wherein the diameter of the 3D printing filament is 1.75±0.05mm or 2.85±0.05mm.
[0015] Optionally, the desalination treatment includes water washing or weak acid washing; the drying treatment temperature is 80-120℃ and the drying time is 6-24h; the calcination activation treatment temperature is 500-850℃ and the calcination time is 0.5-4h; the D50 particle size of the powder obtained in step S3 is 1-15μm and the D90 particle size is less than 35μm.
[0016] These features and advantages of the present invention will be disclosed in detail in the following specific embodiments and accompanying drawings. The preferred embodiments or means of the present invention will be shown in detail in conjunction with the accompanying drawings, but are not intended to limit the technical solutions of the present invention. In addition, each of these features, elements and components appearing in the following text and drawings is a plurality of, and different symbols or numbers are used for convenience of representation, but all represent parts with the same or similar construction or function. Attached Figure Description
[0017] The present invention will be further described below with reference to the accompanying drawings: Figure 1 This is a schematic diagram showing the state of the powder matrix and the thermoplastic resin matrix in the prior art without surface modification. Figure 2 This is a schematic diagram showing the state of the modified solid waste mineral powder and the thermoplastic resin matrix in this invention. Figure 3 This is a schematic diagram of the melt extrusion molding of the 3D printed composite material in this invention.
[0018] The components are: 1. thermoplastic resin matrix; 2. powder body; 3. organic modification layer. Detailed Implementation
[0019] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described are intended to explain the present invention and should not be construed as limiting the invention.
[0020] The terms "an embodiment," "example," or "example" used in this specification refer to a particular feature, structure, or characteristic described in connection with the embodiment itself that may be included in at least one embodiment disclosed in this application. The phrase "in an embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment.
[0021] This application provides a 3D printing composite material comprising a thermoplastic resin matrix 1 and modified solid waste mineral powder dispersed in the thermoplastic resin matrix 1. The thermoplastic resin matrix 1 is a continuous resin phase capable of softening or melting under heating conditions and re-solidifying upon cooling, serving to support the modified solid waste mineral powder and form a melt-extrudeable material matrix. The modified solid waste mineral powder, derived from mineral solid waste, is disposed as a dispersed phase within the thermoplastic resin matrix 1 and undergoes pretreatment and surface modification before being melt-blended with the thermoplastic resin matrix 1. By first processing the solid waste mineral powder into a modified powder suitable for melt extrusion systems and then dispersing it in the thermoplastic resin matrix 1, mineral solid waste can be incorporated into the thermoplastic 3D printing material system as a filler component, thus providing a foundation for subsequent fused deposition modeling, particle extrusion, or screw extrusion additive manufacturing of the 3D printing composite material.
[0022] Specifically, such as Figure 1As shown, in the prior art, the unmodified powder body 2 does not have an organic modified layer 3 formed by the action of a surface modifier on its surface. When the unmodified powder body 2 comes into contact with the thermoplastic resin matrix 1, there is a lack of an effective interfacial transition structure between the powder particle surface and the resin matrix, and the powder particles tend to exist in an agglomerated state, which is not conducive to their uniform dispersion in the thermoplastic resin matrix 1. Figure 2 As shown, the modified solid waste mineral powder in this application includes a powder body 2 and an organic modification layer 3 formed on the surface of the powder body 2. The powder body 2 is powder particles obtained by pretreatment of solid waste mineral powder, which is used to provide a mineral filling skeleton; the organic modification layer 3 is formed on the surface of the powder body 2 to change the interfacial state of the powder surface, making it more suitable for co-melting with the thermoplastic resin matrix 1. That is, the powder body 2 and the organic modification layer 3 together constitute the modified solid waste mineral powder. Therefore, during the melt blending process, the modified solid waste mineral powder does not directly enter the resin matrix in the form of untreated bare mineral particles, but rather contacts the resin matrix in the form of particles with the organic modification layer 3 on the surface. As a result, the interfacial transition between the powder particles and the resin matrix is smoother, which helps to reduce the agglomeration and interfacial debonding of the powder in the resin, and allows the composite material to maintain a more stable flow and molding state during melt extrusion.
[0023] The powder body 2 is obtained by pretreatment of solid waste mineral powder. This pretreatment includes impurity removal, desalination, thermal activation, and particle size control. The solid waste mineral powder is derived from mineral-based solid waste, such as one or more of coal gangue, fly ash, steel slag, furnace slag, red mud, siliceous alumina construction waste, ceramic waste, and glass powder. This type of powder typically contains mineral oxide components such as SiO2, Al2O3, CaO, Fe2O3, and MgO. In some embodiments, the total content of these oxides is not less than 60 wt%. By limiting the solid waste mineral powder to mineral-based solid waste and further limiting its main mineral oxide components, the powder system of this application can be distinguished from biomass fillers such as wood flour, straw powder, and pulp powder, and also from single glass fiber reinforced systems, thereby making the resulting composite material more suitable for reflecting the filling and utilization characteristics of mineral-based solid waste.
[0024] Impurity removal processes can include crushing, screening, and magnetic separation of mineral solid waste. Crushing transforms lumpy, flaky, or agglomerated solid waste into smaller particles for subsequent washing, drying, calcination, and ball milling. Screening removes large particles, ensuring a more uniform particle size for subsequent processes. Magnetic separation removes ferromagnetic impurities or some metallic inclusions, particularly suitable for solid waste containing metallic impurities such as steel slag, coal gangue, and fly ash. These impurity removal processes reduce the adverse effects of coarse particles and metallic impurities on subsequent ball milling, melt blending, and nozzle extrusion, making the resulting powder bulk 2 more suitable for producing thermoplastic 3D printing composite materials.
[0025] Desalination can be performed using water washing or weak acid washing. For solid waste mineral raw materials with high soluble salt content, water washing can be used to remove the soluble salts; for solid waste mineral raw materials with high free alkali content, weak acid washing can be used to reduce the free alkali content. After desalination, the solid fraction can be recovered through filtration, sedimentation, centrifugation, or other solid-liquid separation methods. Desalination reduces the chloride content and soluble salt residue in solid waste mineral powder, minimizing the instability caused by these impurities during melt processing and printing, and making the usage conditions of the powder in thermoplastic resin systems more controllable. In some embodiments, the chloride content of the treated modified solid waste mineral powder is less than 1.0 wt%, thereby making the powder more suitable for use in 3D printing materials requiring continuous extrusion.
[0026] Thermal activation treatment can include drying and calcination activation. Drying can be carried out at 80–120℃ for 6–24 hours to reduce the moisture content of solid waste mineral raw materials. Moisture content is an important indicator affecting the stability of thermoplastic melt extrusion materials. If the powder has a high moisture content, bubbles and voids are easily generated during melt blending or printing extrusion. By drying the powder to a moisture content below 1.0 wt%, the powder enters the melt blending equipment in a low-moisture state, which is beneficial to improving the extrusion stability of the composite material. Calcination activation can be carried out at 500–850℃ for 0.5–4 hours. Calcination activation allows the solid waste mineral powder to obtain a more stable thermal state during heat treatment and provides a more suitable powder base for subsequent mechanical ball milling and surface modification. In addition, since thermal activation is carried out after desalination and before particle size control, it both inherits the previous impurity and salt control and provides a foundation for subsequent particle size control and surface modification.
[0027] In addition, particle size control can be achieved through mechanical ball milling. Mechanical ball milling refers to using ball milling media to collide, shear, and grind the calcined product, thereby controlling the particle size distribution of the solid waste mineral powder to a range suitable for melt extrusion 3D printing. In some embodiments, the rotation speed of the mechanical ball milling can be 200–600 rpm, and the milling time can be 0.5–6 h. After particle size control, the D50 particle size of the modified solid waste mineral powder is 1–15 μm, and the D90 particle size is less than 35 μm. Here, D50 represents the particle size corresponding to a cumulative particle size distribution reaching 50%, and D90 represents the particle size corresponding to a cumulative particle size distribution reaching 90%. By simultaneously controlling D50 and D90, both the bulk particle size and the proportion of large particles can be considered, avoiding the impact of a small number of large particles on extrusion stability caused by only controlling the average particle size. This results in the solid waste mineral powder entering the thermoplastic resin matrix 1 having a particle size distribution more suitable for dispersion and extrusion, reducing the risk of local clogging and molding defects caused by large particles.
[0028] The organic modified layer 3 is formed by the surface interaction between a surface modifier and the powder matrix 2. The surface modifier may include one or more of silane coupling agents, titanate coupling agents, aluminate coupling agents, stearic acid, and dopamine. Silane coupling agents may be selected from KH550, KH560, or KH570, etc., and the specific selection can be determined according to the type of thermoplastic resin matrix 1 and the processing temperature. The surface modification treatment can be carried out at 60–120℃ for 0.5–3 hours. During the treatment, the powder matrix 2, after particle size control, can be mixed with the surface modifier, allowing the surface modifier to adsorb, coat, couple, or otherwise interact with the powder surface, thereby forming the organic modified layer 3 on the surface of the powder matrix 2. This organic modified layer 3 does not exist as a separate bulk continuous layer, but rather as an interfacial modified structure formed on the surface of the powder particles. Therefore, in the subsequent melt blending process, the organic modified layer 3 is located between the powder body 2 and the thermoplastic resin matrix 1, making the surface state of the powder closer to the resin processing system, which is beneficial to improving the dispersion state and interfacial bonding state of the powder in the resin matrix.
[0029] In some embodiments, the 3D printed composite material comprises, by weight, 45-85 parts of thermoplastic resin matrix 1, 10-45 parts of modified solid waste mineral powder, 3-15 parts of toughening agent, 2-8 parts of compatibilizer, 0.2-2 parts of lubricant, 0.1-1 parts of antioxidant, and 0-5 parts of functional additives, wherein the organic modified layer 3 is formed by 0.5-3 parts of surface modifier. The above weight range allows the thermoplastic resin matrix 1 to act as a continuous phase to coat and support the modified solid waste mineral powder, while ensuring a sufficient filling ratio of the modified solid waste mineral powder. If the amount of modified solid waste mineral powder is too low, the utilization of mineral solid waste will be limited; if the amount of modified solid waste mineral powder is too high, the melt flow and continuous extrusion stability of the resulting composite material may be affected. By controlling the thermoplastic resin matrix 1 and the modified solid waste mineral powder within the above range, a better balance can be achieved between powder filling utilization and thermoplastic extrusion molding.
[0030] The thermoplastic resin matrix 1 may include one or more of polylactic acid, recycled polyethylene terephthalate, polyethylene terephthalate, polybutylene adipate / terephthalate, polybutylene succinate, polyhydroxyalkanoates, and polypropylene carbonate. Polylactic acid has good applicability to melt deposition modeling; polyethylene terephthalate and recycled polyethylene terephthalate are suitable for forming composite materials with certain toughness and dimensional stability; polybutylene adipate / terephthalate, polybutylene succinate, polyhydroxyalkanoates, polypropylene carbonate, etc., can be selected according to the material's toughness, degradability, or processing window requirements. By selecting the above-mentioned thermoplastic resin matrix 1, the composite material can form a flowable melt when heated and a solidified structure after cooling, thereby meeting the basic material requirements of melt deposition modeling, particle extrusion molding, or screw extrusion additive manufacturing.
[0031] Toughening agents may include one or more of polybutylene adipate / terephthalate, polybutylene succinate, thermoplastic polyurethane, ethylene-vinyl acetate copolymer, and acrylate elastomers. The toughening agent, together with the thermoplastic resin matrix 1, forms the resin phase of the composite material, and its function is to regulate the toughness and fracture response of the composite material. Since the addition of solid waste mineral powder as an inorganic dispersed phase may increase the rigidity and brittleness of the material, introducing an appropriate amount of toughening agent into the formulation can provide better deformation buffer space when the material is subjected to tension, bending, or impact, thereby improving the impact resistance of the composite material and the overall toughness of the printed product, making the material more suitable for preparing 3D printed products with certain load-bearing or assembly requirements.
[0032] Compatibilizers may include one or more of the following: maleic anhydride-grafted polylactic acid, maleic anhydride-grafted polyethylene, maleic anhydride-grafted polypropylene, epoxy chain extenders, and acrylate copolymers. The compatibilizer is placed between the resin matrix, toughening agent, and modified solid waste mineral powder to adjust the interfacial compatibility between different components. For systems containing polylactic acid, maleic anhydride-grafted polylactic acid can be used; for systems containing polyolefin-based compatibility structures, maleic anhydride-grafted polyethylene or maleic anhydride-grafted polypropylene can be used; for systems requiring adjustment of polyester resin melt strength or segmental interactions, epoxy chain extenders or acrylate copolymers can be used. By introducing compatibilizers, the phase interface between the resin matrix and the modified powder can be made more stable, thereby helping to reduce interfacial defects caused by the dispersed phase of the powder.
[0033] Lubricants can include one or more of polyethylene wax, zinc stearate, calcium stearate, ethylene bis-stearamide, and silicone powder. During melt blending and extrusion, lubricants help regulate the flow friction between the material and the equipment walls, and between powder particles and the resin melt. Since composite materials containing mineral powders need to maintain continuous flow during twin-screw extrusion, single-screw wire extrusion, or nozzle extrusion, an appropriate amount of lubricant can facilitate smoother material transport and plasticization within the processing equipment. In other words, lubricants regulate the flow resistance of composite materials during melt processing, thereby promoting stable extrusion and wire forming.
[0034] Antioxidants may include one or more of hindered phenolic antioxidants or phosphite antioxidants. Hindered phenolic antioxidants can inhibit excessive oxidative degradation of the resin matrix during hot processing, while phosphite antioxidants can be used in combination with hindered phenolic antioxidants to improve hot processing stability. Since the composite material of this application needs to undergo heating processes such as melt blending, extrusion, pelletizing, wire extrusion, and printing extrusion, the addition of antioxidants can reduce the performance fluctuations of the thermoplastic resin matrix 1 during repeated heating processes, thereby improving the processing stability of the composite material and enabling the material to maintain a relatively stable resin phase structure during melt blending and printing.
[0035] Functional additives may include one or more of the following: biochar, bamboo charcoal powder, lignin, nano-silica, nano-calcium carbonate, flame retardants, antibacterial agents, UV stabilizers, or deodorizers. The dosage of functional additives can be 0-5 parts; that is, functional additives may not be added if additional functions are not required, and may be added to adjust appearance, odor, weather resistance, flame retardancy, or other functions. Since functional additives are not essential components for forming the thermoplastic resin matrix 1, modified solid waste mineral powder, and organic modified layer 3, they exist as adjustable components and can be selected according to the specific application of the printed product. Functional additives enable the composite material to maintain its basic melt extrusion molding capability while allowing for functional expansion based on the product's application scenario.
[0036] This embodiment also provides a method for preparing 3D printing composite materials. The method includes steps S1 to S6. In step S1, mineral solid waste is sequentially subjected to crushing, screening, magnetic separation, and desalination to obtain desalinated solid waste mineral raw materials. Crushing can be performed using jaw crushers, hammer crushers, or roller crushers to transform lumpy solid waste into screenable particles; screening can be performed using vibrating screens or air classifiers to remove coarse particles unsuitable for subsequent ball milling and extrusion; magnetic separation can be performed using dry or wet magnetic separation to remove ferromagnetic particles; desalination can be performed using water washing or weak acid washing. Through step S1, the solid waste mineral raw materials entering subsequent heat treatment and ball milling processes have lower impurities and salt interference, thus providing a prerequisite for obtaining printable powder.
[0037] In step S2, the desalinated solid waste mineral raw material undergoes drying and calcination activation treatment to obtain the calcined product. The drying treatment can be carried out at 80–120℃ for 6–24 hours to reduce the free and adsorbed water content in the raw material. The calcination activation treatment can be carried out at 500–850℃ for 0.5–4 hours to complete the heat treatment of the solid waste mineral raw material before it enters the ball mill and surface modification. The drying treatment, occurring before the calcination activation treatment, reduces the fluctuations in moisture content caused in the initial stage of high-temperature treatment; the calcination activation treatment, occurring before particle size control, allows the heat-treated material to be further refined in the ball mill. Through the operation of step S2, the solid waste mineral raw material undergoes moisture and thermal state adjustment before entering the melt blending system, which helps to reduce the impact of moisture and thermal instability factors on the extrusion process.
[0038] In step S3, the calcined product is mechanically ball-milled to obtain powder body 2. Mechanical ball milling can be performed using a planetary ball mill, drum ball mill, vibratory mill, or other equipment capable of refining the powder. After ball milling, the D50 particle size of powder body 2 obtained in step S3 is 1–15 μm, and the D90 particle size is less than 35 μm. Through this step, the calcined product is controlled to become a micron-sized powder suitable for thermoplastic resin dispersion and extrusion. Since 3D printed composite materials typically require nozzle extrusion in fused deposition modeling and continuous forming through an extrusion orifice in particle extrusion or screw extrusion additive manufacturing, controlling the powder particle size and large particle content can directly reduce the risk of localized accumulation and extrusion fluctuations.
[0039] In step S4, a surface modifier is used to modify the surface of the powder body 2 to form an organic modified layer 3 on the surface of the powder body 2, thereby obtaining modified solid waste mineral powder. Specifically, the powder body 2 can be placed in a high-speed mixer, a heating and stirring device, or other powder modification equipment, and the surface modifier is added and treated at 60–120°C for 0.5–3 hours. During the treatment, the surface modifier interacts with the surface of the powder body 2, forming an organic modified layer 3 on the powder surface. This step occurs after mechanical ball milling and before melt blending, thus allowing the powder particles with the target particle size to undergo interface conditioning before entering the resin melt. Through the operation of step S4, the modified solid waste mineral powder can be dispersed in the thermoplastic resin matrix 1 as modified particles during subsequent melt blending, thereby improving the interfacial bonding between the powder and the resin matrix.
[0040] In step S5, the thermoplastic resin matrix 1, modified solid waste mineral powder, toughening agent, compatibilizer, lubricant, and antioxidant are mixed to obtain a mixture. The mixing process can be carried out in a high-speed mixer, low-speed agitator, or other solid material mixing equipment, and the mixing time can be 5–30 minutes. In this step, the thermoplastic resin matrix 1 provides the continuous phase, the modified solid waste mineral powder provides the mineral filler phase, the toughening agent adjusts the toughness of the composite material, the compatibilizer adjusts the interfacial state between components, the lubricant adjusts the melt processing flow state, and the antioxidant adjusts the thermal processing stability. By premixing before melt blending, the components can form a more uniform solid mixture state before entering the extruder, thereby improving the subsequent melt blending efficiency.
[0041] In step S6, the mixture is melt-blended, extruded, cooled, pelletized, and dried to obtain granular 3D printing composite material. Melt blending can be performed using a twin-screw extruder, with an extrusion temperature of 150–260°C and a screw speed of 50–300 rpm. The twin-screw extruder melts the thermoplastic resin matrix 1 under heating and shearing, and disperses the modified solid waste mineral powder, toughening agent, compatibilizer, lubricant, and antioxidant in the resin melt. After cooling, the extrudate forms strips, which are then pelletized and dried to obtain granular 3D printing composite material. The granular material can be used directly as a raw material for pellet extrusion 3D printing or as an intermediate raw material for filament extrusion. Through step S6, the composite material of this application can be obtained through continuous melt blending and pelletizing processes, facilitating subsequent storage, transportation, and printing processing.
[0042] In some embodiments, step S7 is included after step S6, where the granular 3D printing composite material is extruded into 3D printing filament using a single-screw extruder. The filament diameter can be 1.75±0.05 mm or 2.85±0.05 mm. The single-screw extruder remelts the granular composite material and then sizing, cooling, drawing, and winding it into a continuous filament. By further processing the granular composite material into filaments of the aforementioned diameter, the composite material can be adapted to commonly used fused deposition modeling (FDM) equipment. Because the filament diameter remains within a predetermined range, the feeding mechanism of the printing equipment can stably clamp and transport the filament, thereby facilitating continuous printing.
[0043] The 3D printing composite material of this application can be used in fused deposition modeling, particle extrusion molding, or screw extrusion additive manufacturing. When used in fused deposition modeling, the process is as follows: Figure 3As shown, the heating and melting zone is used to heat the granular 3D printing composite material or 3D printing filament to a molten or softened state. The molten composite material is extruded through the nozzle and deposited layer by layer to form printed layers. Adjacent printed layers bond together to form an interlayer stack structure. The printing temperature (i.e., the temperature of the heating and melting zone) can be 180–260°C, the heated bed temperature can be 40–90°C, and the printing speed can be 20–120 mm / s. The printing temperature is used to keep the thermoplastic resin matrix 1 in a molten or flowable state, the heated bed temperature is used to provide relatively stable bottom layer adhesion conditions in the early stages of printing, and the printing speed is used to match the material melt supply and the interlayer stacking process. By adapting the material to the above printing conditions, the composite material can be used in common thermoplastic melt extrusion additive manufacturing equipment. It should be noted that the heated bed refers to a printing platform used to support the printed product and can be heated. During the fused deposition modeling process, the nozzle extrudes the molten or softened 3D printing composite material onto the heated bed. The heated bed maintains a predetermined temperature, ensuring that the initial printed layers adhere relatively stably to the printing platform and reducing the risk of warping or detachment of the printed product from the printing platform.
[0044] The resulting 3D printing composite material can be made into granules or filaments depending on the printing method. When used for granule extrusion molding or screw extrusion additive manufacturing, the granular 3D printing composite material obtained in step S6 can be directly used as printing material; when used for fused deposition modeling, the granular 3D printing composite material can be further made into filaments with a diameter of 1.75±0.05mm or 2.85±0.05mm. Thus, the same material system can be adapted to different fused deposition modeling additive manufacturing methods without changing the basic principle of melt blending modified solid waste mineral powder with thermoplastic resin matrix 1 to form composite materials.
[0045] Example 1: This example provides a 3D printing composite material based on polylactic acid and modified coal gangue-based solid waste mineral powder. By weight, the 3D printing composite material comprises 70 parts polylactic acid, 20 parts modified coal gangue-based solid waste mineral powder, 6 parts poly(adipate / butylene terephthalate), 3 parts maleic anhydride-grafted polylactic acid, 0.5 parts ethylene bis-stearamide, 0.3 parts antioxidant 1010, and 0.2 parts nano-silica; wherein the organic modification layer 3 of the modified coal gangue-based solid waste mineral powder is formed by 1 part KH570 silane coupling agent. Polylactic acid (PLA) serves as the thermoplastic resin matrix 1, forming a continuous phase that can be melt-extruded. Modified coal gangue-based solid waste mineral powder is dispersed in PLA as the dispersed phase. Poly(butylene adipate / terephthalate) is used as a toughening agent to adjust the toughness of the composite material. Maleic anhydride-grafted PLA serves as a compatibilizer to adjust the interfacial state between PLA and modified coal gangue-based solid waste mineral powder. Ethylene bis-stearamide serves as a lubricant to improve the material flow state during melt blending and extrusion. Antioxidant 1010 is used to improve the thermal stability of PLA during melt processing. Nano-silica is added as a functional additive to adjust the overall performance of the composite material.
[0046] In the preparation process, coal gangue is crushed and screened to remove large particulate impurities and obtain solid waste mineral raw materials suitable for subsequent processing. The screened coal gangue is then washed with water to remove soluble salts and fine mud impurities, resulting in desalted coal gangue raw materials. The desalted coal gangue raw materials are dried at 105℃ for 12 hours to reduce their moisture content. The dried coal gangue raw materials are then calcined at 700℃ for 2 hours to obtain calcined products. The calcined products are mechanically ball-milled to form coal gangue-based powder body 2 with a D50 particle size of 8μm and a D90 particle size of less than 30μm. This powder particle size distribution falls within the range suitable for use in melt extrusion 3D printing materials, reducing the risk of localized blockage or filament fluctuations caused by large particles during subsequent extrusion and printing.
[0047] Then, the coal gangue-based powder body 2 was mixed with KH570 silane coupling agent and surface modified at 90°C for 1 hour. This allowed the KH570 silane coupling agent to interact with the surface of the coal gangue-based powder body 2, thereby forming an organic modification layer 3 on the surface of the coal gangue-based powder body 2, resulting in modified coal gangue-based solid waste mineral powder. This organic modification layer 3, located on the surface of the coal gangue-based powder body 2, can improve the interfacial contact between the powder particles and the polylactic acid matrix during subsequent melt blending, making the powder easier to disperse in the continuous resin phase.
[0048] Polylactic acid (PLA), modified coal gangue-based solid waste mineral powder, poly(adipate) / butylene terephthalate (PET), maleic anhydride-grafted PLA, ethylene bis-stearamide, antioxidant 1010, and nano-silica were added to a high-speed mixer and mixed for 15 minutes to obtain a mixture. Subsequently, the mixture was added to a twin-screw extruder for melt blending at an extrusion temperature of 165–195°C and a screw speed of 120 rpm. During melt blending, PLA melted upon heating to form a continuous resin phase, while the modified coal gangue-based solid waste mineral powder was dispersed within the continuous resin phase under the shearing and conveying action of the screw. After cooling, pelletizing, and drying, the extrudate yielded granular 3D printing composite material. Further, this granular 3D printing composite material was processed into 3D printing filaments with a diameter of 1.75 mm using a single-screw extruder. The resulting filament was fused deposition modeling (FDM) printed under conditions of nozzle temperature 200–215℃, heated bed temperature 50–60℃, and printing speed 50 mm / s. During printing, filament output was stable, with no significant clogging or warping. Testing revealed that the printed sample exhibited a tensile strength of 48.6 MPa, an elongation at break of 8.5%, a flexural strength of 72.4 MPa, a flexural modulus of 2680 MPa, and a notched impact strength of 4.8 kJ / m². Therefore, this embodiment demonstrates that by desalting, thermally activating, controlling particle size, and modifying the surface of coal gangue powder, it can be stably dispersed within a polylactic acid matrix and is suitable for FDM printing.
[0049] Example 2: This example provides a 3D printing composite material based on recycled polyethylene terephthalate and modified coal gangue-based solid waste mineral powder. By weight, the 3D printing composite material comprises 68 parts recycled polyethylene terephthalate, 22 parts modified coal gangue-based solid waste mineral powder, 5 parts thermoplastic polyurethane, 3 parts epoxy-functionalized acrylate copolymer, 1 part multifunctional epoxy chain extender, 0.6 parts ethylene bis-stearamide, 0.2 parts antioxidant 1010, and 0.2 parts antioxidant 168; wherein the organic modification layer 3 of the modified coal gangue-based solid waste mineral powder is formed by KH560 silane coupling agent. Recycled polyethylene terephthalate is used as the thermoplastic resin matrix 1 to form a continuous phase with a high processing temperature window; thermoplastic polyurethane is used as a toughening agent to improve the toughness of the composite material; epoxy-functionalized acrylate copolymer and multifunctional epoxy chain extender are used to adjust the resin phase and powder interface state; ethylene bis-stearamide is used to adjust the flow state during melt extrusion; antioxidant 1010 and antioxidant 168 are used to improve the thermal stability of the material during high-temperature melt processing.
[0050] In the preparation process, coal gangue is sequentially crushed, screened, and magnetically separated to remove coarse and magnetic impurities. It is then washed with water to reduce the soluble salt content, resulting in desalted coal gangue raw material. The desalted coal gangue raw material is dried at 105℃ for 12 hours and then calcined at 700℃ for 2 hours to obtain the calcined product. The calcined coal gangue is then mechanically ball-milled to achieve a D50 particle size of 7 μm and a D90 particle size of less than 30 μm, yielding coal gangue-based powder body 2. This particle size range allows the powder to be more suitable for dispersion in recycled polyethylene terephthalate melt and reduces the impact of large particles on the stability of wire extrusion.
[0051] Subsequently, the coal gangue-based powder body 2 was surface modified using KH560 silane coupling agent to form an organic modification layer 3 on its surface, resulting in modified coal gangue-based solid waste mineral powder. Since the organic modification layer 3 formed by the KH560 silane coupling agent is located on the surface of the powder body 2, it can improve the interfacial bonding state between the powder and the recycled polyethylene terephthalate matrix during melt blending. The recycled polyethylene terephthalate was vacuum dried at 100℃ for 8 hours, and the modified coal gangue-based solid waste mineral powder was dried at 105℃ for 4 hours. Then, the recycled polyethylene terephthalate, modified coal gangue-based solid waste mineral powder, thermoplastic polyurethane, epoxy-functionalized acrylate copolymer, multifunctional epoxy chain extender, ethylene bis-stearamide, antioxidant 1010, and antioxidant 168 were added in proportion to a high-speed mixer and mixed for 15 minutes to obtain a mixture.
[0052] The mixture was melt-blended in a twin-screw extruder at an extrusion temperature of 210–240°C and a screw speed of 150 rpm. The extruded material was cooled, pelletized, and dried to obtain granular 3D printing composite material, which was then processed into 1.75 mm diameter 3D printing filaments using a single-screw filament extruder. The resulting filaments were fused deposition modeling (FDM) at a nozzle temperature of 235–250°C, a heated bed temperature of 75–85°C, and a printing speed of 50 mm / s. The printing process was continuous and stable, and the printed products exhibited good toughness and dimensional stability. Testing showed that the printed samples had a tensile strength of 45.2 MPa, an elongation at break of 16.5%, a flexural strength of 64.7 MPa, a flexural modulus of 2360 MPa, and a notched impact strength of 8.3 kJ / m². This embodiment demonstrates that pretreated and surface-modified coal gangue-based solid waste mineral powders are suitable for use in recycled polyethylene terephthalate systems and can be prepared into wires that meet the requirements of fused deposition modeling.
[0053] Example 3: This example provides a 3D printing composite material based on recycled polyethylene terephthalate and modified fly ash. By weight, the 3D printing composite material comprises 65 parts recycled polyethylene terephthalate, 25 parts modified fly ash, 5 parts thermoplastic polyurethane, 3 parts maleic anhydride-grafted polyethylene, 0.5 parts zinc stearate, 0.3 parts antioxidant 168, and 0.2 parts bamboo charcoal powder; wherein the organic modification layer 3 of the modified fly ash is formed by 1 part titanate coupling agent. Recycled polyethylene terephthalate (PET) serves as the thermoplastic resin matrix 1, enabling the formation of a continuously extruded melt under heating conditions. Modified fly ash is used as the dispersed phase of solid waste mineral powder to realize the filling and utilization of mineral solid waste in 3D printing materials. Thermoplastic polyurethane is used as a toughening agent to adjust the toughness of the material. Maleic anhydride-grafted polyethylene is used as a compatibilizer to adjust the interfacial state between the resin matrix and the powder. Zinc stearate is used as a lubricant to improve the flowability during melt extrusion. Antioxidant 168 is used to improve the thermal processing stability. Bamboo charcoal powder is added as a functional additive to impart additional functions to the material.
[0054] In the preparation process, fly ash is sieved and magnetically separated to remove unburned carbon and ferromagnetic impurities; subsequently, it is washed with water to reduce the soluble salt content. The washed fly ash is dried at 105℃ for 12 hours and calcined at 600℃ for 1 hour to obtain calcined fly ash. The calcined fly ash is then mechanically ball-milled to control its D50 particle size to approximately 5 μm and its D90 particle size to less than 25 μm, resulting in fly ash powder body 2. This particle size control process reduces the impact of larger particles in the fly ash on the melt extrusion process, making the fly ash more suitable for inclusion in the thermoplastic resin matrix 1.
[0055] Then, the surface of the fly ash powder body 2 was modified using a titanate coupling agent, allowing the titanate coupling agent to interact with the fly ash surface and form an organic modified layer 3 on the surface of the fly ash powder body 2, thus obtaining modified fly ash. Recycled polyethylene terephthalate was vacuum dried at 100℃ for 8 hours, and then mixed with modified fly ash, thermoplastic polyurethane, maleic anhydride-grafted polyethylene, zinc stearate, antioxidant 168, and bamboo charcoal powder in a specific ratio to obtain a mixture. Subsequently, the mixture was added to a twin-screw extruder for melt blending at an extrusion temperature of 210–240℃ and a screw speed of 150 rpm. After cooling, pelletizing, and drying, the extrudate was processed into 3D printing filaments with a diameter of 1.75 mm using a single-screw wire extruder.
[0056] The obtained filament was fused deposition modeled under conditions of nozzle temperature 235–245℃, hot bed temperature 70–80℃, and printing speed 60 mm / s. The printed product had a continuous and uniform surface with good interlayer bonding. Testing showed that the printed sample had a tensile strength of 43.8 MPa, an elongation at break of 18.6%, a flexural strength of 61.5 MPa, a flexural modulus of 2150 MPa, and a notched impact strength of 7.9 kJ / m². In this embodiment, fly ash was desalinated, thermally activated, particle size controlled, and surface modified to form modified fly ash, enabling it to be dispersed as a modified solid waste mineral powder in a recycled polyethylene terephthalate matrix, thereby improving the compatibility of fly ash in fused extrusion 3D printing materials.
[0057] Example 4: This example provides a 3D printing composite material based on polylactic acid, polybutylene succinate, and modified steel slag powder. By weight, the 3D printing composite material comprises 55 parts polylactic acid, 15 parts polybutylene succinate, 20 parts modified steel slag powder, 5 parts acrylate toughening agent, 2 parts epoxy chain extender, 1 part polyethylene wax, 0.3 parts antioxidant 1010, and 0.7 parts lignin; wherein the organic modification layer 3 of the modified steel slag powder is formed by 1 part silane coupling agent. Polylactic acid and polybutylene succinate together constitute the thermoplastic resin matrix 1, which is used to form the continuous phase of the composite material; modified steel slag powder serves as the dispersed phase of solid waste mineral powder; acrylate toughening agents are used to improve the toughness of the composite material; epoxy chain extenders are used as compatibilizers to adjust the interface state of the resin phase and powder; polyethylene wax is used as a lubricant to improve the flow state during melt blending and extrusion; antioxidant 1010 is used to improve the thermal processing stability; lignin is added as a functional additive to adjust the additional performance of the composite material.
[0058] In the preparation process, the steel slag is crushed, sieved, and magnetically separated to remove free iron particles and coarse impurities. It is then washed with water to reduce the free alkali content, resulting in desalted steel slag raw material. The desalted steel slag raw material is dried at 105℃ and then calcined at 800℃ for 2 hours to obtain calcined steel slag. The calcined steel slag is then mechanically ball-milled to obtain steel slag powder body 2 with a D50 particle size of 10μm and a D90 particle size of less than 35μm. By controlling the particle size of the steel slag powder within the above range, it can be made more suitable for dispersion in thermoplastic resin melts and the influence of coarse particles on the melt extrusion process can be reduced.
[0059] Subsequently, the steel slag powder body 2 was surface modified using a silane coupling agent, allowing the silane coupling agent to interact with the surface of the steel slag powder and form an organic modified layer 3 on the surface of the steel slag powder body 2, thus obtaining modified steel slag powder. Polylactic acid, polybutylene succinate, modified steel slag powder, acrylate toughening agent, epoxy chain extender, polyethylene wax, antioxidant 1010, and lignin were added to a high-speed mixer and mixed evenly. Then, the mixture was melt-blended using a twin-screw extruder at an extrusion temperature of 160–200°C and a screw speed of 130 rpm. The resulting particles were dried and prepared into 3D printing filaments with a diameter of 1.75 mm.
[0060] The obtained filament was fused deposition modeling (FDM) printing under conditions of nozzle temperature 205–220℃, heated bed temperature 55–65℃, and printing speed 50 mm / s. The printing process was continuous and stable, and the printed products exhibited good rigidity and dimensional stability. Testing showed that the printed sample had a tensile strength of 39.7 MPa, an elongation at break of 13.2%, a flexural strength of 57.6 MPa, a flexural modulus of 2420 MPa, and a notched impact strength of 6.5 kJ / m². In this embodiment, steel slag powder was processed through crushing, sieving, magnetic separation, desalination, thermal activation, ball milling, and surface modification to form modified steel slag powder, enabling the steel slag to be used as a solid waste mineral powder in thermoplastic melt extrusion 3D printing composite materials.
[0061] Example 5: This example provides a 3D printing composite material based on polylactic acid, polybutylene adipate / terephthalate, and modified building ceramic waste powder. By weight, the 3D printing composite material comprises 60 parts polylactic acid, 10 parts polybutylene adipate / terephthalate, 22 parts modified building ceramic waste powder, 4 parts ethylene-vinyl acetate copolymer, 2 parts maleic anhydride-grafted polylactic acid, 0.5 parts calcium stearate, and antioxidant 1010; wherein the organic modification layer 3 of the modified building ceramic waste powder is formed by 1 part KH560 silane coupling agent. Polylactic acid and poly(butylene adipate) terephthalate (PAT) together serve as the thermoplastic resin matrix 1, forming a continuous resin phase that can be melt-extruded; modified building ceramic waste powder serves as the dispersed phase of solid waste mineral powder; ethylene-vinyl acetate copolymer serves as a toughening agent, used to adjust the toughness of the material; maleic anhydride-grafted polylactic acid serves as a compatibilizer, used to adjust the interfacial state between the powder and the resin matrix; calcium stearate serves as a lubricant, used to improve the flow state during melt processing; and antioxidant 1010 serves to improve the stability of the resin matrix during melt processing.
[0062] In the preparation process, the building ceramic waste is crushed, sieved, and magnetically separated to remove large particles and metallic impurities. It is then washed with water to reduce the soluble salt content, resulting in desalted building ceramic waste raw material. The desalted raw material is dried and calcined to obtain a calcined product. This calcined product is then mechanically ball-milled to obtain building ceramic waste powder body 2. Through this pretreatment, the building ceramic waste is transformed from blocky or coarse-particle solid waste into micron-sized powder suitable for melt blending with thermoplastic resins. Subsequently, the surface of the building ceramic waste powder body 2 is modified using KH560 silane coupling agent to form an organic modified layer 3 on its surface, resulting in modified building ceramic waste powder.
[0063] Polylactic acid (PLA), polybutylene adipate / terephthalate (PAT), modified building ceramic waste powder, ethylene-vinyl acetate copolymer, maleic anhydride-grafted PLA, calcium stearate, and antioxidant 1010 are mixed and then melt-blended using a twin-screw extruder. During the melt blending process, the thermoplastic resin matrix 1 is heated to form a melt, and the modified building ceramic waste powder is dispersed in the resin melt under the shearing action of the screw. After cooling, pelletizing, and drying, the extrudate yields a granular 3D printing composite material. This granular 3D printing composite material can be further processed into 3D printing filaments using a single-screw extruder, or it can be used directly as a raw material for granular extrusion 3D printing. In this embodiment, the building ceramic waste powder, as a source of mineral solid waste, is pretreated and surface-modified before entering the thermoplastic resin matrix 1. This avoids the dispersion and extrusion stability problems that occur when untreated ceramic waste powder is directly added to the resin, enabling building ceramic waste to be used in thermoplastic melt extrusion 3D printing composite materials.
[0064] Comparative Example 1: This comparative example is basically the same as Example 1, except that the coal gangue powder was only crushed, sieved, dried and ball-milled, without calcination activation treatment or surface modification treatment using KH570 silane coupling agent. Therefore, no organic modification layer 3 was formed on the surface of the coal gangue powder. In other words, the powder with thermoplastic resin matrix 1 added in this comparative example is unmodified coal gangue powder, rather than modified solid waste mineral powder composed of the powder body 2 and the organic modification layer 3 formed on its surface.
[0065] By weight, the 3D printing composite material of this comparative example comprises 70 parts polylactic acid (PLA), 20 parts unmodified coal gangue powder, 6 parts poly(butylene adipate / terephthalate), 3 parts maleic anhydride-grafted PLA, 0.5 parts ethylene bis-stearamide, 0.3 parts antioxidant 1010, and 0.2 parts nano-silica. PLA serves as the thermoplastic resin matrix 1, unmodified coal gangue powder as the dispersed phase of solid waste mineral powder, poly(butylene adipate / terephthalate) as a toughening agent, maleic anhydride-grafted PLA as a compatibilizer, ethylene bis-stearamide as a lubricant, antioxidant 1010 as an antioxidant, and nano-silica as a functional additive.
[0066] In the preparation process, coal gangue is crushed and sieved, then dried and mechanically ball-milled to obtain coal gangue powder. Then, polylactic acid, unmodified coal gangue powder, poly(butylene adipate / terephthalate), maleic anhydride-grafted polylactic acid, ethylene bis-stearamide, antioxidant 1010, and nano-silica are added to a high-speed mixer and mixed to obtain a mixture. This mixture is then prepared into 3D printing filaments under the same melt blending, extrusion, cooling, pelletizing, drying, and filament extrusion conditions as in Example 1, and printed templates are prepared under the same fused deposition modeling conditions as in Example 1.
[0067] Because the coal gangue powder in this comparative example did not undergo calcination activation treatment and surface modification treatment, no organic modified layer 3 was formed on the powder surface. Therefore, when it was directly melt-blended with the polylactic acid matrix, the dispersion and interfacial bonding of the powder in the resin matrix were not as good as in Example 1. During the printing process, the extrusion stability of the filament and the interlayer bonding performance of the printed product both decreased. Tests showed that the tensile strength of the printed sample was 33.5 MPa, the elongation at break was 3.2%, the flexural strength was 46.8 MPa, the flexural modulus was 2190 MPa, and the notched impact strength was 2.7 kJ / m². Compared with Example 1, the elongation at break and notched impact strength of this comparative example were significantly reduced, indicating that calcination activation treatment and surface modification treatment play an important role in improving the dispersion and interfacial bonding of coal gangue powder in the thermoplastic resin matrix 1.
[0068] Comparative Example 2: This comparative example is basically the same as Example 3, except that unmodified fly ash is used as the solid waste mineral powder, and thermoplastic polyurethane, maleic anhydride-grafted polyethylene, and titanate coupling agent are not added. That is to say, the fly ash in this comparative example has not undergone surface modification treatment, and an organic modified layer 3 is not formed on the surface of the fly ash; at the same time, this comparative example does not contain the toughening agent and compatibilizer corresponding to Example 3.
[0069] By weight, the 3D printing composite material in this comparative example comprises 65 parts recycled polyethylene terephthalate, 25 parts unmodified fly ash, 0.5 parts zinc stearate, 0.3 parts antioxidant 168, and 0.2 parts bamboo charcoal powder. Recycled polyethylene terephthalate serves as the thermoplastic resin matrix 1, unmodified fly ash as the dispersed phase of solid waste mineral powder, zinc stearate as a lubricant, antioxidant 168 as an antioxidant, and bamboo charcoal powder as a functional additive.
[0070] In preparation, fly ash was subjected to sieving, magnetic separation, water washing, drying, calcination, and ball milling according to the fly ash pretreatment conditions in Example 3, but without using titanate coupling agent for surface modification treatment of the fly ash. Subsequently, recycled polyethylene terephthalate, unmodified fly ash, zinc stearate, antioxidant 168, and bamboo charcoal powder were mixed to obtain a mixture. This mixture was then used to prepare printed samples according to the same melt blending, granulation, wire extrusion, and fused deposition modeling printing conditions as in Example 3.
[0071] Because this comparative example did not form an organic modified layer 3 on the fly ash surface and did not add toughening agents and compatibilizers, the interfacial bonding between the fly ash and the recycled polyethylene terephthalate matrix was weak, resulting in decreased material toughness and interlayer bonding performance. During the printing process, the filament brittleness increased, and localized filament breakage and insufficient interlayer bonding occurred. Tests showed that the tensile strength of the printed sample was 29.8 MPa, the elongation at break was 4.1%, the flexural strength was 41.6 MPa, the flexural modulus was 1980 MPa, and the notched impact strength was 2.9 kJ / m². Compared with Example 3, the tensile strength, flexural strength, and notched impact strength of this comparative example were significantly reduced, indicating that surface modification, toughening agents, and compatibilizers play an important role in improving the interfacial bonding performance, toughness, and interlayer bonding performance of fly ash-based thermoplastic 3D printing composite materials.
[0072] Comparative Example 3: This comparative example is basically the same as Example 2, except that the ball milling treatment of the coal gangue-based solid waste mineral powder was insufficient. The resulting powder had a D50 particle size of approximately 22 μm and a D90 particle size greater than 50 μm, failing to meet the particle size control requirements of 1–15 μm for the D50 particle size and less than 35 μm for the D90 particle size of the modified solid waste mineral powder. Apart from the difference in powder particle size, the types and amounts of thermoplastic resin matrix 1, toughening agent, compatibilizer, lubricant, antioxidant, and surface modifier in this comparative example are basically the same as in Example 2.
[0073] In the preparation process, coal gangue was sequentially crushed, sieved, magnetically separated, washed, dried, and calcined to obtain a calcined product. The calcined product was then subjected to a short-term mechanical ball milling process to obtain a coal gangue-based powder body 2 with a relatively large particle size. Subsequently, the coal gangue-based powder body 2 was surface-modified using KH560 silane coupling agent to form an organic modification layer 3 on its surface, resulting in a modified coal gangue-based solid waste mineral powder with a relatively large particle size. Then, recycled polyethylene terephthalate, the modified coal gangue-based solid waste mineral powder with a relatively large particle size, thermoplastic polyurethane, epoxy-functionalized acrylate copolymer, multifunctional epoxy chain extender, ethylene bis-stearamide, antioxidant 1010, and antioxidant 168 were mixed, and printed samples were prepared under the same melt blending, wire extrusion, and fused deposition modeling printing conditions as in Example 2.
[0074] Because the modified coal gangue-based solid waste mineral powder in this comparative example has a relatively large particle size and wide particle size distribution, even with the formation of an organic modification layer 3 on the powder surface, its dispersion uniformity and continuous extrusion compatibility in the thermoplastic resin matrix 1 are still affected. Intermittent filament ejection fluctuations and localized nozzle blockages occurred during printing, and large particle defects were found in some areas of the printed product's cross-section. Testing showed that the tensile strength of the printed sample was 34.2 MPa, the elongation at break was 5.8%, the flexural strength was 48.9 MPa, the flexural modulus was 2240 MPa, and the notched impact strength was 3.6 kJ / m². Compared to Example 2, the notched impact strength and printing stability of this comparative example decreased, indicating that particle size control of the solid waste mineral powder plays a crucial role in the continuous extrusion and stable printing of composite materials.
[0075] It should be noted that in the above embodiments and comparative examples, the tensile strength and elongation at break of the printed samples can be tested according to the GB / T 1040 series standards; the flexural strength and flexural modulus can be tested according to GB / T 9341; and the notched impact strength can be tested according to GB / T 1843. The printed samples are prepared by fused deposition modeling from the 3D printing filaments obtained in the corresponding embodiments or comparative examples. The printing temperature, heated bed temperature, and printing speed are based on the corresponding printing conditions in each embodiment. At least five parallel samples are tested for each group of samples, and the average value is taken as the test result. The test results are shown in Table 1.
[0076] Table 1. Mechanical property test results of the printed strips obtained in the examples and comparative examples. ; The results show that the 3D printing composite materials obtained in Examples 1 to 5 all exhibit good comprehensive performance, with tensile strengths exceeding 30 MPa, flexural strengths exceeding 45 MPa, and notched impact strengths exceeding 4.0 kJ / m², meeting the requirements for mechanical properties and molding stability of fused deposition modeling (FDM) 3D printing materials. Compared with the comparative example, the solid waste mineral powder, after desalination, calcination activation, particle size control, and surface modification, can be dispersed in the thermoplastic resin matrix 1 as modified solid waste mineral powder with an organic modification layer 3 on the surface, thereby improving the powder dispersion and interfacial bonding. Furthermore, the toughening agent, compatibilizer, lubricant, and antioxidant play roles in toughness regulation, interface regulation, processing flow regulation, and thermal stability regulation in the composite material system, respectively, enabling the material to maintain good processing adaptability and printing stability during melt blending, filament extrusion, and fused deposition modeling.
[0077] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes, but is not limited to, the contents described in the accompanying drawings and the specific embodiments above. Any modifications that do not depart from the functional and structural principles of the present invention will be included within the scope of the claims.
Claims
1. A 3D printing composite material, characterized in that, It includes a thermoplastic resin matrix and modified solid waste mineral powder dispersed in the thermoplastic resin matrix; The thermoplastic resin matrix is recycled polyethylene terephthalate; The modified solid waste mineral powder includes a powder body and an organic modification layer formed on the surface of the powder body; The powder body is obtained by pretreatment of solid waste mineral powder derived from coal gangue. The pretreatment includes impurity removal treatment, desalination treatment, thermal activation treatment and particle size control treatment. The D50 particle size of the powder body is 7μm and the D90 particle size is less than 30μm. The organic modified layer is formed by surface modification of the powder body using KH560 silane coupling agent; By weight, the 3D printing composite material comprises 68 parts of the recycled polyethylene terephthalate, 22 parts of the modified solid waste mineral powder, 5 parts of thermoplastic polyurethane, 3 parts of epoxy-functionalized acrylate copolymer, 1 part of multifunctional epoxy chain extender, 0.6 parts of ethylene bis-stearamide, 0.2 parts of antioxidant 1010, and 0.2 parts of antioxidant 168; The above components are melt-blended to form the 3D printing composite material.
2. A method for preparing a 3D printed composite material as described in claim 1, characterized in that, Includes the following steps: S1, the coal gangue is subjected to crushing, screening and magnetic separation in sequence, and then washed with water to obtain desalinated coal gangue raw material; S2, the desalted coal gangue raw material is dried at 105°C for 12 hours and then calcined at 700°C for 2 hours to obtain the calcined product; S3, the calcined product is subjected to mechanical ball milling to obtain a powder body with a D50 particle size of 7μm and a D90 particle size of less than 30μm; S4, KH560 silane coupling agent is used to perform surface modification treatment on the powder body to form an organic modification layer on the surface of the powder body, thereby obtaining modified solid waste mineral powder. S5, the recycled polyethylene terephthalate is vacuum dried at 100°C for 8 hours, and the modified solid waste mineral powder is dried at 105°C for 4 hours; Subsequently, the recycled polyethylene terephthalate, the modified solid waste mineral powder, thermoplastic polyurethane, epoxy-functionalized acrylate copolymer, multifunctional epoxy chain extender, ethylene bis-stearamide, antioxidant 1010 and antioxidant 168 are added to a high-speed mixer according to the weight proportions described in claim 1 and mixed for 15 minutes to obtain a mixture. S6, the mixture is added to a twin-screw extruder for melt blending, extrusion, cooling, pelletizing and drying to obtain granular 3D printing composite material, wherein the extrusion temperature is 210-240℃ and the screw speed is 150rpm.
3. The preparation method according to claim 2, characterized in that, The process includes step S7 after step S6, in which the granular 3D printing composite material is extruded into 3D printing filament using a single screw extruder. The diameter of the 3D printing filament is 1.75 mm.
Citation Information
Patent Citations
High strength fused deposition material with ceramic texture and preparation method thereof
CN110330267A
Coal gangue powder and fly ash composite master batch and preparation method thereof
CN121554924A